Faktor Penyebab Rendahnya Keikutsertaan Suami dalam Metode Operasi Pria (MOP) di Desa Gebang Kec. Patrang Kab. Jember - Ayu Puteri Nur Perdani (Jurnal MID-Z (MIDWIFERI ZIGOT), 2018)
Men assume that family planning is a matter of women, and because of worry if the male surgery method KB (MOP) will disturb the harmony of husband and wife relationship, they are afraid of decreased sexual arousal. The purpose of the study was to determine the factors that led to the low participation of husbands in the Male Operation Method (MOP) in Gebang Village, Patrang District, Jember Regency. The research method uses descriptive. The population of all husbands from fertile age couples (PUS) is 324. Sampling uses simple random sampling. The sample was a number of husbands from couples of childbearing age (EFA number 32 people. Variables that cause low participation of husbands in Male Operating Methods (MOP). Data collection using data processing questionnaires using editing, coding, scoring, tabulating. Results of personal factor in Gebang Village, Patrang District, Jember Regency, 20 respondents (62.5%) aged ? 30 years, 21 respondents (65.6%) the smallest age ? 2 years, 18 respondents (56.3%) the number of children> 2 people. Whereas for cultural factors that support 8 respondents (25%) and those that do not support 24 respondents (75%). It can be concluded that the factors that cause the low participation of husbands in male surgery methods (MOP) are influenced by cultural factors that do not support.The midwife is expected to give IEC to the husband of PUS about the use of male surgery method of contraception (MOP) and all matters related to the use of male surgery method of contraception (MOP) including how to use, advantages and disadvantages of the male surgery method (MOP) and demonstration directly use of male surgery contraception (MOP) method.